2015
DOI: 10.1007/s00403-015-1577-8
|View full text |Cite
|
Sign up to set email alerts
|

In silico database screening of potential targets and pathways of compounds contained in plants used for psoriasis vulgaris

Abstract: Reviews and meta-analyses of clinical trials identified plants used as traditional medicines (TMs) that show promise for psoriasis. These include Rehmannia glutinosa, Camptotheca acuminata, Indigo naturalis and Salvia miltiorrhiza. Compounds contained in these TMs have shown activities of relevance to psoriasis in experimental models. To further investigate the likely mechanisms of action of the multiple compounds in these TMs, we undertook a computer-based in silico investigation of the proteins known to be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Some clinical trials have been conducted by employing natural products to examine the effect of psoriasis mitigation. The meta-analysis of the clinical trials demonstrates that aloe vera, indigo naturalis, kukui nut oil, Mahonia aquifolium , and capsaicin are the most efficacious topical phytomedicines for treating psoriasis [56,57]. These natural products can ameliorate psoriatic lesions via the molecular mechanisms that are related to apoptosis, angiogenesis inhibition, and inflammation suppression [58].…”
Section: The Trend In Using Natural Products As Antipsoriatic Agentsmentioning
confidence: 99%
“…Some clinical trials have been conducted by employing natural products to examine the effect of psoriasis mitigation. The meta-analysis of the clinical trials demonstrates that aloe vera, indigo naturalis, kukui nut oil, Mahonia aquifolium , and capsaicin are the most efficacious topical phytomedicines for treating psoriasis [56,57]. These natural products can ameliorate psoriatic lesions via the molecular mechanisms that are related to apoptosis, angiogenesis inhibition, and inflammation suppression [58].…”
Section: The Trend In Using Natural Products As Antipsoriatic Agentsmentioning
confidence: 99%
“…Danshen exhibited anti-inflammatory and anti-proliferative functions in psoriasis studies (Zhang et al, 2014;May et al, 2015). In silico screening revealed that Danshen contained compounds modulating apoptosis regulator Bcl-2, Bcl-2-Associated X, Caspase-3 along with TNF-α and Prostaglandin G/H synthase 2 (May et al, 2015). Salvianolic acid B reduced psoriatic changes by inhibiting psoriatic inflammatory and keratin markers by abolishing PI3K/Akt signaling pathway (Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In order to build the compound-target interaction profiles in XCHT and Heshouwu , we analyzed the chemical compounds and protein interactions integrated from the Search Tool for Interactions of Chemicals and Proteins (STITCH) 5.0 database ( ) and Herbal Ingredients’ Targets (HIT) Database ( ), which are both databases of known and predicted interactions between chemicals and proteins. These databases were based on text mining and molecular docking technology to predict compound-protein interaction, which has been applied in the research of TCM for discovering potential active ingredients and interpreting molecular mechanisms of herbal medicines [ 46 , 47 ]. The STITCH 5.0 database can be used to study potential interactions between 300,000 phytochemicals and 2.6 million proteins curated from 1133 organisms.…”
Section: Methodsmentioning
confidence: 99%